2012
DOI: 10.1093/molbev/mss261
|View full text |Cite
|
Sign up to set email alerts
|

Pig Domestication and Human-Mediated Dispersal in Western Eurasia Revealed through Ancient DNA and Geometric Morphometrics

Abstract: Zooarcheological evidence suggests that pigs were domesticated in Southwest Asia ∼8,500 BC. They then spread across the Middle and Near East and westward into Europe alongside early agriculturalists. European pigs were either domesticated independently or more likely appeared so as a result of admixture between introduced pigs and European wild boar. As a result, European wild boar mtDNA lineages replaced Near Eastern/Anatolian mtDNA signatures in Europe and subsequently replaced indigenous domestic pig lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
142
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 38 publications
16
142
0
1
Order By: Relevance
“…The same people may have later intentionally dispersed the European haplotype into the Levant during the Iron Age. Indeed, the major turnover in the Near Eastern pig population took place around 900 BC, when the European haplotype became predominant in the Southern Levant (Meiri et al, 2013), in Anatolia (Ottoni et al, 2013) and Romania (Evin et al, 2015). A similar scenario has been proposed for the Eastern Mediterranean origin of cattle in Etruria (Central Italy) introduced in this region by navigation during the Late Bronze (Pellecchia et al, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…The same people may have later intentionally dispersed the European haplotype into the Levant during the Iron Age. Indeed, the major turnover in the Near Eastern pig population took place around 900 BC, when the European haplotype became predominant in the Southern Levant (Meiri et al, 2013), in Anatolia (Ottoni et al, 2013) and Romania (Evin et al, 2015). A similar scenario has been proposed for the Eastern Mediterranean origin of cattle in Etruria (Central Italy) introduced in this region by navigation during the Late Bronze (Pellecchia et al, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…In an attempt to clarify the timeline of the population dynamics of Near Eastern pigs, Ottoni et al (2013) used a powerful approach based on the analysis of ancient mitochondrial DNA and dental geometric and morphometric data obtained from 393 specimens from 48 archaeological sites. In doing so, they demonstrated that the European Neolithic pig remains carried NE2 haplotypes that are native to Anatolia, thus identifying this geographic location as the main centre of Near Eastern pig dispersal into Europe (Figure 1).…”
Section: The Fertile Crescent and China As The Main Centres Of Pig Domentioning
confidence: 99%
“…Thus, the development of techniques that allow for the high-throughput sequencing of ancient nuclear DNA would be crucial to circumvent this limitation. Currently, the number of ancient populations sampled is quite limited, and we have explored only the mitochondrial variation within these populations (Larson et al, 2007b;Ottoni et al, 2013). Third-generation sequencing platforms, which allow for the sequencing of single DNA molecules without an intermediary amplification step, may have a fundamental role in characterizing the autosomal genomes of ancient pig specimens (Rizzi et al, 2012).…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…However, new models of domestication suggest that while spatial separation of wild and domestic types is often sought, various domestic species ranging from pigs to horses have also been cross‐bred for specific characteristics by allowing controlled introgression from wild herds. (Ottoni, 2013; Jónsson, 2014; Frantz, 2015). For most domestic breeds, this idea remains a hypothesis as the original free‐ranging wild forms have become largely extinct or restricted to a few isolated areas (Clutton‐Brock, 1987).…”
Section: Introductionmentioning
confidence: 99%